Computer Based Acquisitions System at Texas A&I University - Ned C. Morris (Information Technology and Libraries, 1968)
In September 1966, a system was initiated at the University which provides for the use of automatically produced multiple orders and for the use of change chards to update order information on previously placed orders already on disk storage. The system is geared to an IBM 1620 Central Proessing Unit (40K) which has processed a total of 10,222 order transactions the first year. It is believed that the system will lend itself to further development within its existing framework and that it will be capable of handling future work loads.